2015
DOI: 10.1002/col.22004
|View full text |Cite
|
Sign up to set email alerts
|

Research on filter selection method for broadband spectral imaging system based on ancient murals

Abstract: Digitization of cultural heritage protection has received considerable attention in heritage studies and spectral imaging technology has been playing an important role in this research. This article aims to study the technique of selecting optimal filter set to obtain ancient murals spectral image with high spectral and colorimetric accuracy based on the broadband spectral imaging system. The 330 Dunhuang murals mineral pigment color patches and the GretagMacbeth ColorChecker (CC) as well as 27 pieces of optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Different from the type of multichannel spectra recovery imaging systems where both the number of channels and the spectral sensitivity functions of them are often different from each other, 24‐28 the digital camera‐based spectra recovery system based on single RGB image has common features; they all have three imaging channels (Red, Green, and Blue) to simulate the color perception of human visual system. The research carried by Jiang et al showed that the spectral sensitivity functions of different brands of digital cameras all have similar distribution shape, 29 and it is accurate enough to estimate the spectral sensitivity functions of a digital camera using only the first two dimension of eigenvectors of spectral sensitivity functions database.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Different from the type of multichannel spectra recovery imaging systems where both the number of channels and the spectral sensitivity functions of them are often different from each other, 24‐28 the digital camera‐based spectra recovery system based on single RGB image has common features; they all have three imaging channels (Red, Green, and Blue) to simulate the color perception of human visual system. The research carried by Jiang et al showed that the spectral sensitivity functions of different brands of digital cameras all have similar distribution shape, 29 and it is accurate enough to estimate the spectral sensitivity functions of a digital camera using only the first two dimension of eigenvectors of spectral sensitivity functions database.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…erefore, it is widely employed in digital acquisition, archives, and exhibition of cultural heritages since it can endow cultural heritages with eternal virtual life. Our team has also constructed a multispectral imaging system and applied it to the digital acquisition of ancient wall paintings [6]. So far, we have obtained many visible spectral images from Mogao Grottoes of Dunhuang.…”
Section: Introductionmentioning
confidence: 99%
“…So far, we have obtained many visible spectral images from Mogao Grottoes of Dunhuang. For details about the images, please refer to our report [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the demand to recover spectral reflectance is increasing due to more precise and accurate color representation. Many related industries will obtain large benefits from several applications, including the color reproduction of traditional printing, color management in publishing, digital archiving of artworks, and digital compositing in the film industry . Although the spectral data provide more useful information on color properties than trichromatic representation, it is difficult to measure in usual cases because of the high cost of instruments, the geometrical limitation in a scene, and the special materials needed .…”
Section: Introductionmentioning
confidence: 99%